Administrative Management Strategy at SMK Timika City - Stefanus Stefason; Ulul Albab; Eny Haryati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Vocational education in Indonesia faces a serious challenge in the form of a gap between the competencies of Vocational High School (SMK) graduates and the evolving needs of the workforce. Timika City, despite having the largest number of vocational high schools (SMK) in Papua, has not yet fully demonstrated optimal educational management quality, particularly in the aspect of school administration. This condition has resulted in low effectiveness in data recording, documentation of industrial work practices, and reporting and evaluation of partnerships with the business and industrial world (DUDI). This study aims to explore and analyze administrative management strategies that can improve educational quality while strengthening the work readiness of vocational high school students in Timika City. The research method used is a descriptive qualitative approach with content analysis of secondary data, including government policy reports, educational statistics, and the latest scientific literature. The results show that weaknesses in the administrative system are one of the factors inhibiting the achievement of competitive vocational education quality. The implementation of management strategies based on Total Quality Management (TQM) principles, particularly through the Plan–Do–Check–Act (PDCA) cycle, data-driven decision-making, and the involvement of all school elements, has proven effective in increasing the efficiency and accountability of administrative services. The discussion also emphasized the importance of transformational leadership from school principals, developing the competencies of administrative staff, utilizing information technology in administrative systems, and strengthening strategic partnerships with the industrial and industrial sectors (DUDI). Therefore, it can be concluded that school administrative management is not merely a technical function, but rather a strategic component in building a vocational education ecosystem that is adaptive, relevant, and oriented to the needs of the workplace. This research recommends that school policymakers and local governments strengthen administrative governance systems to support educational quality and improve the job readiness of vocational high school graduates.